STRATEGI PROMOSI DESTINASI AGROWISATA KEBUN TEH DINAS PARIWISATA DAN KEBUDYAAN KABUPATEN GOWA DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH - Jannah. A, Miftahul; Muttaqin, Andi; Idris, Muhammad (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
Tourism is one of the main sectors in increasing state income in Indonesia. Indonesia, which is an archipelagic country, has abundant natural wealth with a variety of cultures, customs, and religions where these natural wealth can be utilized in the field of tourism as a commodity sector that is very good for the economy and as a foreign exchange earner of the country second only to petroleum and natural gas. This study aims to find out the strategy of promoting tea garden agrotourism destinations and to find out what the role of the Gowa Regency Tourism and Culture Office is in awakening tea garden agrotourism destinations. This study used a descriptive qualitative approach, with the location of the first research, the Gowa District Tourism and Culture Office and the second, Malino Highlands Tea Garden located in Tinggimoncong District, Gowa Regency. Data collection is by means of data collection, reduction, data presentation and drawing conclusions. The results showed that the promotion strategy carried out by the Malino Tea Garden Agrotourism Destination in Increasing Regional Original Income is to collaborate with travel agency agents, banners, spreading through social media such as Websites, Twitter, TikTok, Instagram, and Facebook, installation of tourist locations on goggle maps, and from some information conveyed by customers who have come to the Malino Tea Garden Agrotourism location to potential customers through word of mouth. The role of the Gowa Regency Tourism and Culture Office in Awakening The Agrotourism of Malino Tea Garden includes development and promotion, facilities and infrastructure, and environmental management strategies.